13C NMR study on carbamate hydrolysis reactions in aqueous amine/CO2 solutions. (January 2021) - Wada, Sakurako; Kushida, Takayuki; Itagaki, Haruna; Shibue, Toshimichi; Kadowaki, Haruna; Arakawa, Jun; Furukawa, Yukio
Highlights: Equilibrium constants of carbamate hydrolysis reactions were determined. The equilibrium constants were determined using 13 C NMR and equilibrium analysis. Gibbs energies of carbamate hydrolysis reactions for AMP and IPAE were negative. Gibbs energies of carbamate hydrolysis reactions for MEA and DEA were positive. Enthalpy changes of carbamate hydrolysis reactions were determined. Abstract: Carbamates of primary or secondary amines play a central role in amine CO2 absorbents. The equilibrium constant of a carbamate hydrolysis reaction, K ch, is important for evaluating the performance of absorbents. However, few K ch values have been reported to date. We determined the K ch values of normal amines, such as monoethanolamine (MEA), diethanolamine (DEA), and hindered amines, such as 2-amino-2-methyl-1-propanol (AMP) and 2-(isopropylamino)ethanol (IPAE), using a method involving a combination of 13 C NMR spectroscopy and a chemical equilibrium analysis. The Gibbs energy changes derived from K ch for AMP and IPAE at 25 °C were negative, whereas those for normal amines, MEA and DEA, were positive. These properties are characteristic of hindered amines. We determined the standard enthalpy and entropy changes of the carbamate hydrolysis reactions from the temperature dependence of the equilibrium constant. The equilibrium constants and standard enthalpies obtained using the present method will be valuable for evaluating the performance of amine CO2 absorbents.